2022
DOI: 10.1038/s41598-022-24463-4
|View full text |Cite
|
Sign up to set email alerts
|

Fracture fragment of the condyle determines the ramus height of the mandible in children with intracapsular condylar fractures treated conservatively

Abstract: This study aimed to explore and impart understanding of bone remodelling in children with intracapsular fractures treated conservatively. Records of children (less than 12 years), who sustained intracapsular fractures and treated conservatively, were retrieved consecutively for the period of March 2011 to February 2016. Data about age, gender, date of injury, dates of admission and discharge, mechanism of trauma, location and pattern of fracture, other mandibular fractures, treatment methods and time of review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…We have previously shown that the fracture fragment of the condyle determines the ramus height of the mandible in children with condylar head fractures treated conservatively. 5 During follow-up, the absorption of the lateral process of the condyle after closed treatment became close to the 'horizontal absorption' until the height (or articular surface) of the lateral condylar process dropped and aligned with the articular surface of the medial process. Closed treatment could not restore the fracture fragment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We have previously shown that the fracture fragment of the condyle determines the ramus height of the mandible in children with condylar head fractures treated conservatively. 5 During follow-up, the absorption of the lateral process of the condyle after closed treatment became close to the 'horizontal absorption' until the height (or articular surface) of the lateral condylar process dropped and aligned with the articular surface of the medial process. Closed treatment could not restore the fracture fragment.…”
Section: Discussionmentioning
confidence: 97%
“…During follow-up, all displaced condylar fragments fused with the ramus stump at the displaced position. The lateral process of the condyle was also found to be resorbed seriously close to the ‘horizontal absorption’ until the height (or articular surface) of the lateral condylar process dropped and aligned with the articular surface of the medial process 5…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…But it also provides a growth center for mandible 2,3,4 . Any injury to the condyle during growing age will result in mandibular growth disruption 3,5,6 . Condylar fractures are quite common among children.…”
Section: Introductionmentioning
confidence: 99%
“…Condylar fractures are quite common among children. According to previously conducted studies, condylar fracture represents 11% to 16% of all facial fractures during young age 5,7,8 . In another study, con-dylar neck was found to be the most frequent site of fracture (55%) in patients younger than twelve years of age 2 .…”
Section: Introductionmentioning
confidence: 99%